Use of foreign experience in hotel business - Umurzaqova Gulnora Abdubannopovna (THE INNOVATION ECONOMY, 2026)
This article analyzes the theoretical and practical aspects of using the experience of foreign countries in the development of the hotel business. In particular, foreign practices in the areas of service quality, management system, innovative approaches, marketing strategies and human resource management are studied, and the possibilities of their application in the conditions of Uzbekistan are highlighted.